Optimalisasi Kualitas Layanan Transportasi Publik: Pendekatan Model P-Transqual dalam Mengevaluasi Kinerja di PO. Moedah - Dunga Dwi Barinta; Yetty Dwi Lestari; Ariefky Pramudya Kharisma (Penerbit Goodwood, 2024)
Purpose: This study aims to quantify and scrutinize the caliber of public transportation services through meticulous application of the Public Transportation Quality (P-TRANSQUAL) framework. Methodology: The proposed research method involves a qualitative approach that integrates the use of Public Transportation Service Quality (PTSQ) and fishbone diagrams. The research population consisted of users of PO Moedah services, selected randomly based on predetermined inclusion criteria, including diverse age groups, gender, occupation, and monthly income range.Results: The empirical findings suggest that, while functionally proficient, the public transportation services administered by PO Moedah are not immune to deficiencies, warranting remedial intervention.Conclusions: He need for public transportation services in Indonesia is very high because people want time efficiency and a reduction in problems such as congestion and accidents.Limitations: The study was limited by subjective customer opinions and potential sample bias due to inclusion criteria such as age and income. Additionally, the findings are specific to PO Moedah's area and offer only a snapshot in time, limiting the generalizability and long-term relevance.Contribution: This study offers practical insights for PO Moedah to improve services and demonstrates the use of the P-TRANSQUAL framework to assess public-transportation quality. It highlights the importance of customer satisfaction and promotes sustainable urban transportation by addressing key issues, such as fuel consumption and traffic congestion.